2012
DOI: 10.1016/j.jclepro.2012.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide diffusion of the global reporting initiative: what is the point?

Abstract: a b s t r a c tThis study analyzes the worldwide diffusion of the Global Reporting Initiative (GRI) from the viewpoint of both a macro-and a microanalysis using data from the first decade of this century. For the macroanalysis, logistic curves were used to demonstrate the different stages and patterns in the dissemination of GRI in the different regions of the world that were examined. For the microanalysis, two indicesdinstability and concentrationdwere used to analyze and assess GRI diffusion across differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
195
3
67

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(273 citation statements)
references
References 69 publications
8
195
3
67
Order By: Relevance
“…In other words, although much research has been conducted at a macro level, the specific indicators in sustainability reports have been largely ignored. This creates a need for further research (Roca and Searcy, 2012), especially of in-depth business cases to analyse the impacts of the adoption of social standards (Marimon et al, 2012). Furthermore, even studies on mining at the micro level have not focused on the quality of the data reported.…”
Section: Gri Reporting In Mining and The Issue Of Data Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, although much research has been conducted at a macro level, the specific indicators in sustainability reports have been largely ignored. This creates a need for further research (Roca and Searcy, 2012), especially of in-depth business cases to analyse the impacts of the adoption of social standards (Marimon et al, 2012). Furthermore, even studies on mining at the micro level have not focused on the quality of the data reported.…”
Section: Gri Reporting In Mining and The Issue Of Data Qualitymentioning
confidence: 99%
“…Facing these concerns, corporate social responsibility (CSR) and triple bottom line-driven sustainability reporting with a view to community relations have emerged as a crucial strategic consideration for mining corporations (Jenkins and Yakovleva, 2006) to show what they are doing (Marimon et al, 2012) and with expectations of gaining a better global competitive position by doing so (Vintró et al, 2012). Nonetheless, the role and impacts of CSR by mining corporations in developing countries is a matter of an active debate where polarised positions prevail (Hilson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the variety of information potentially included within CSD has asked different initiatives in order to systematize the contents of disclosure and to improve its capacity to be respondent to the needs of any given stakeholder group. These efforts include the ISO 14001, SA8000, ISO 26000, the United Nations Global Compact (UNGC) and Sullivan's Global Principles [19]. The same objective was behind the work of The Coalition for Environmentally Responsible Economies (CERES) and the Tellus Institute.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it has attracted considerable research interest in order to unveil and identify the regional-cultural or sectoral trajectories of disclosure practices (e.g. see recent insights by Sardinha et al, 2011;Lozano and Huisingh, 2011;Roca and Searcy, 2012;Sobhani et al, 2012;Lodhia, 2012;Marimon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, France, Spain, the Netherlands, the UK, Sweden and Denmark have introduced legal requirements to enlarge the scope of conventional corporate accounting and reporting to include non-financial performance parameters. While voluntary disclosure has gained momentum among large for-profit entities (Marimon et al, 2012), still being the most recognized form of non-financial reporting, global trends indicate the further expansion of legally mandated disclosure to new countries in the near future (KPMG, 2010). These market-based, societal and regulatory developments explain the growth of corporate NFD and also encapsulate its driving forces and conceptual underpinnings.…”
Section: Introductionmentioning
confidence: 99%